Online Processing of Subject–Verb–Object Order in a Diverse Sample of Mandarin‐Exposed Preschool Children with Autism Spectrum Disorder. Issue 12 (11th August 2019) - Su, Yi (Esther); Naigles, Letitia R.
Abstract: Grammatical comprehension remains a strength in English‐exposed young children with autism spectrum disorder (ASD), yet limited research has investigated how preschool children with ASD process grammatical structures in real time, in any language. Using the eye‐movement measures of Intermodal Preferential Looking, we assessed online processing of subject–verb–object (SVO) order in seventy 2‐ to 5‐year‐old children with ASD exposed to Mandarin Chinese across the spectrum, whose vocabulary production scores were dramatically delayed compared with the typical controls. With this Mandarin‐exposed sample, we tested the extent to which children with ASD require (a) highly consistent input and/or (b) good discourse/pragmatics for acquiring grammatical structures. Children viewed side‐by‐side videos depicting reversible actions (e.g., a bird pushing a horse vs. a horse pushing a bird), and heard an audio matching only one of those actions; their eyegaze to each video was coded and analyzed. Both typically developing children and children with ASD demonstrated comprehension of SVO word order, suggesting that core grammatical structures such as basic word order may be preserved in children with ASD across languages despite radical differences in language environment, social/pragmatic abilities, and neurological organization. However, children with ASD were less efficient in online sentence processing than typical children, and the efficiency of their online sentence processing was related to their standardized language assessment scores. Of note is that across both Mandarin Chinese and English, some proportion of minimally verbal children with ASD exhibited SVO comprehension despite their profoundly impaired expressive language skills. Autism Res 2019, 12: 1829–1844 . © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay summary: Grammar is a strength in the language comprehension of young English learners with autism spectrum disorder (ASD). Eye‐movement data from a diverse sample of Chinese preschoolers with ASD indicated similar grammatical strength of basic word order in Chinese (e.g., to understand sentences like "The bird is pushing the horse"). Moreover, children's proficiency of sentence processing was related to their language assessment scores. Across languages, such knowledge is even spared in some minimally verbal children with ASD.